The Slavonic Calvinist Reading-Primer in Trinity College Dublin Library Teil 1 - Roberts, Christopher (Specimina philologiae Slavicae, 1986)
The volume represent ed by mss. 1684 and 1694 was given to Trinity College in December 1706 by an alumnus called Alexander Jephson. There is no (...) external information about the provenance, date of composition or authorship of the document... The manuscript consists of 196 pages, formed from eleven 16-page gatherings, one 12-page and finally two 4-page gatherings. Text teilw. Altslaw. Durchsuchbare elektronische Faksimileausgabe als PDF. Digitalisiert im Rahmen des DFG-Projektes Digi20 in Kooperation mit der BSB München.